My First Numbers Let's get counting - Sirett, Dawn; Appleton, Polly; Calver, Susan; Hunt, Rachael Parfitt (London Dorling kindersley, 2011)
Helping children to recognize numbers from 1-12, this text also encourages early numeracy skills. Illustrations explain concepts such as more, fewer, equal, first and last
Arithmetic nations
1 2 13 23
NEW
Keywords: Mathematics